PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA INDUSTRI KECIL BATIK âSIDO MUKTIâ KECAMATAN PLAOSAN KABUPATEN MAGETAN - Srijani, Ninik (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
This study aims to determine employee work motivation Small Industries Batik "SIDO MUKTI" Plaosan Magetan, to determine employee work productivity Small Industries Batik "SIDO MUKTI" Plaosan Magetan, and to know is there any effect of work motivation on employee work productivity Small Industries Batik "SIDO MUKTI" Plaosan Magetan. The samples in this study using saturated sample as many as 34 people are based on all Small Industries Employees Batik "SIDO MUKTI" Plaosan Magetan. Pegumpulan data using questionnaires and documentation methods. In analyzing the data used product moment correlation statistical method to test the validity of the instruments used in regression testing method to test the hypothesis put forward in this study. The results showed that the influence of work motivation at the same time a positive relationship to work productivity Batik Small Industries Employees "SIDO MUKTI" Plaosan Magetan. It is derived from the value of 0.717 while rtabel rhitung of 0.339 (0.717 â¥ 0.339). On the other hand Sighit values of 0.000 and 0.05 Sigprob (0.000 â¤ 0.05) was rejected, meaning that work motivation has a relationship with the Small Industries Employees work productivity Batik "SIDO MUKTI" Plaosan Magetan. It also obtained the F test value , the value of F at 33.830 while the value Ftable 4.149 (33.830 â¥ 4.149). On the other hand Sigprob Sighit of 0.000 and 0.05 (0.000 â¤ 0.05) means there is a denial that shows that there are significant between work motivation on employee work productivity Small Industries Batik "SIDO MUKTI" Plaosan Magetan. Also obtained regression coefficients (t test) with tcount 5.816 while the value ttable 2,037 (5.816 â¥ 2.037). On the other hand Sighit values of 0.000 and 0.05 Sigprob value (0.000 â¤ 0.05). With this was rejected, meaning that there are different influences on the productivity of Small Industries Employees Batik "SIDO MUKTI" Plaosan Magetan. While the results of R2 of 51.40 %, 51.40 % shows that for the variable productivity of employees affected work motivation , while the remaining 48.60 % is influenced by other factors . Furthermore, when seen in the derived regression equation value equation Y = 10.320 + 0.773 X. From the regression equation it can be seen if the motivation to work as much as 1 % increase labor productivity will increase as well of 0.773 %, while the other factors remain.Â Keywords : Work Motivation, Work Productivity